Conceptual modeling of the structure of a geoinformation system for formation of land plots in state and municipal ownership of settlements - Tetiana Bukhalska; Oleksandr Yanchuk; Viktor Moshynskyi; Anatolii Lishchynskyi (Geodesy and Cartography)
The article deals with the issues of automation of land cadastral information processing based on the modern international standards for management and processing of geospatial information. Object-relational databases together with the GIS provide powerful opportunities for collection, systematization, processing, analysis of various data, as well as storage and visualization of spatial information. According to the results of the analysis of the current legislative provision and processing of the existing data based on the international standards of the ISO 19110 series, the research developed a conceptual scheme of the geospatial database for the formation of state and municipal land plots within settlements. The research provides a model for checking the topology of the geospatial database of the system of automated formation of state and municipal land plots within settlements according to the structure and requirements of the international standard “ISO 19107:2019 Geographic information. Spatial schema”. The developed conceptual model and topology verification model are the basis for physical data modeling and allow ensuring the principle of interoperability in the Spatial Data Infrastructure.